2013
DOI: 10.1177/00333549131282s107
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sexual Health in the U.S.: An Inventory of Nationally Representative Surveys and Surveillance Systems

Abstract: Objectives. To identify opportunities within nationally representative surveys and surveillance systems to measure indicators of sexual health, we reviewed and inventoried existing data systems that include variables relevant to sexual health .Methods. We searched for U.S. nationally representative surveys and surveillance systems that provided individual-level sexual health data . We assessed the methods of each data system and catalogued them by their measurement of the following domains of sexual health: kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Globally, the age of sexual debut has decreased while the number of lifetime sexual partners has increased. Previous research and prevention policy has focused on the negative aspects of sexuality such as HIV infection and STIs, sexual power, sexual violence and exploitation while ignoring the positive aspects of sexuality such as quality of sexual experiences, quality of sexual relationships (Welling & Johnson, 2013), sexual communication, and attitudes about sexuality (Ivanovich, Leichliter & Douglas Jr., 2013). Policy makers need to advocate for the develop new tools to measure the positive aspects of sexual health, and lobby for more resources to be allocated for sexual health and wellness (Ivanovich et al, 2013).…”
Section: Implications For Sexual Health Policymentioning
confidence: 99%
“…Globally, the age of sexual debut has decreased while the number of lifetime sexual partners has increased. Previous research and prevention policy has focused on the negative aspects of sexuality such as HIV infection and STIs, sexual power, sexual violence and exploitation while ignoring the positive aspects of sexuality such as quality of sexual experiences, quality of sexual relationships (Welling & Johnson, 2013), sexual communication, and attitudes about sexuality (Ivanovich, Leichliter & Douglas Jr., 2013). Policy makers need to advocate for the develop new tools to measure the positive aspects of sexual health, and lobby for more resources to be allocated for sexual health and wellness (Ivanovich et al, 2013).…”
Section: Implications For Sexual Health Policymentioning
confidence: 99%
“…Moreover, it is unclear how sexual health may promote non-sexual health in young women who choose same-sex partners, or those who choose both same-sex and opposite sex relationships. As acknowledged in existing literature, 39 substantial revisions may need to be made to existing nationally representative surveys in order to reach appropriate numbers of sexual minority youth. We also do not have a clear understanding of how the structure of sexual health and related non-sexual behaviors function in the relationships of young men.…”
Section: Discussionmentioning
confidence: 99%
“…Trading sexual favors for money or other means of support, concurrent sexual partnerships, and being involved in actual or potential partner violence are additional behaviors that have been cited as increasing risk (Whyte, 2005). Measuring sexual health using indicators that are conceptually congruent with its definition is needed to adequately characterize the many issues that may influence sexuality and sexual behavior (Ivankovich, Leichliter, & Douglas Jr., 2013).…”
Section: Overviewmentioning
confidence: 99%
“…Despite ongoing efforts to migrate away from using more traditional measures, in a review of national surveillance systems and health surveys, Ivankovich, Leichliter, and Douglas found that, most data systems and surveys used in the US tend to focus primarily on the behavioral aspects of sexual health including sexual risk or the surveillance of negative health outcomes (2013). Collaborative efforts between individual researchers and the Centers for Disease Control and Prevention have begun to expand the tracking and measurement of sexual health in the US to include pertinent domains involving an individual's level of sexual health education, communication abilities, and sexual approach or attitude (Douglas & Fenton, 2013;Ivankovich et al, 2013). In addition, social-and community-level indicators have been integrated into national surveillance efforts to include sexual behaviors and relationships, health outcomes, and access or utilization of sexual health services (Douglas & Fenton, 2013;Ivankovich et al, 2013).…”
Section: Sexual Healthmentioning
confidence: 99%
See 1 more Smart Citation